The Use of Reserves and Accrued Liabilities for Discretionary Shaping of Financial Results of Stock Exchange Listed Companies: Case of Poland - Anna STASZEL; Pawel ZIENIUK (Communications of International Proceedings, 2020)
Reserves and accruals belong to the measurement category in which a lack of credibility is considered to be at a high-risk value. Due to subjectivity and possibility of choosing many premises during the valuation process, reserves and accruals are treated as instruments of aggressive accounting. Therefore, those items can influence the discretionary shaping of financial results that are presented in financial reports which pose as the final product of the accounting system. The main objective of the empirical research conducted by the Authors was to prove the influence of the decisions - taken by the management of companies listed on the stock exchange - regarding the establishment and release of reserves as well as accruals with the financial result value indicated in the profit and loss statement. The research sample consists of 68 companies listed on the Warsaw Stock Exchange which prepare financial reports in accordance with International Financial Reporting Standards (IFRS). The applied time period is 11 years - reports from 2007 to 2018. Theoretical considerations were conducted with the use of national and international literature regarding the subject, and applicable legal provisions concerning the accounting framework. A review of empirical research on the possibility of manipulating financial results through reserves and accruals was also made. The Authors analysed full versions of 748 financial reports with the inclusion of explanatory notes. T for the average and chi square tests were applied to confirm the statistical significance of the received results. Statistically significant dependences stem from the received results and confirm formulated research hypotheses that entities with high financial results do not avoid establishing reserves, but entities with low financial results release the previously established reserves and thus improve their profit levels. Conclusions that stem from the conducted empirical research take part in the discussion on the credibility of financial reports and on the possibility of using the items from reserves and accruals by the management in order to shape the value of the financial result in a discretionary manner. The results may be a prerequisite for conducting further empirical research that would consist of a larger research sample and that would take into account other tools that can be used for manipulating the value of financial results by companies listed on the stock exchange.
Keywords: Credibility of Financial Reports; Manipulation of Financial Results; Aggressive Accounting; Reserves; Accrued Liabilities.